PERMAINAN TRADISIONAL HIDE AND SEEK DALAM MENSTIMULASI KETRAMPILAN SOSIAL EMOSIONAL ANAK USIA DINI USIA 5-6 TAHUN DI ERA DIGITAL - Surina, Surina; Kristiana, Dian; Irsad Rusdiani, Nurtina (AL IHSAN: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
In the rapidly advancing digital era, young children tend to experience a decline in direct social interaction due to excessive use of technological devices. This article aims to describe and identify the traditional game of hide and seek in stimulating the social-emotional skills of young children aged 5-6 years. This research employs a qualitative approach with a case study research type. The data collection techniques utilize observation, interviews, and documentation conducted at Kemala Bhayangkari Kindergarten. Meanwhile, the data analysis used includes data reduction, data presentation, and conclusion drawing. The research results show that the game of hide and seek can shape social skills such as cooperation, empathy, and communication, as well as help children regulate their emotions through direct play experiences with peers. The habituation of this game regularly over one year also shows an increase in children's involvement in social activities as well as their ability to express feelings and understand the feelings of others. These findings indicate that even amidst the currents of digitalization, traditional games remain relevant and play an important role in supporting the social-emotional development of early childhood. Therefore, there is a need for the integration of traditional games in early childhood education programs as an effort to balance technological development with the holistic developmental needs of children.